Fragments from the history of loss : the nature industry and the postcolony / Louise Green. - Green, Louise, 1968- (The Pennsylvania State University Press, 2020)
"Examines the theoretical framing of "nature" in South Africa and beyond. Analyzes myths and fantasies that have brought the world to a point of climate catastrophe and continue to shape the narratives through which it is understood"-- Provided by publisher.
Keywords: Nature -- Effect of human beings on.; Nature -- Effect of human beings on -- South Africa.; Climatic changes -- Social aspects.; Climatic changes -- Social aspects -- South Africa.; South Africa.